MULTIMODAL ANALYSIS OF A PRINTED ADVERTISEMENT “BURGER KING” - Lubis, Bambang Nur Alamsyah; Asnawi, Asnawi (Universitas PGRI Sumatera Barat, 2024)
This study deals with multimodal analysis of a printed advertisement “Burger King”. The objective of the study is to find out the general structure of Burger King printed advertisement, identifying with multimodal analysis. The source of data is visual or printed advertisement of Burger King that can be found in internet or public area. The data of the research is the content of printed advertisement that focus on kinds of advertisement structure. The reseach design is descriptive qualitative research design. The result of this reeach, there are not all general structure of advertisement by Cheong theory occur in the printed advertisement “Burger King”.